The Role of Makassar in Promoting the Archipelago Spice Route in the XVI–XVII Centuries - Abd Rahman Hamid (Buletin Al-Turas, 2022)
PurposeThis study explored the three roles of Makassar in advancing the archipelago's spice routes: port growth arrangement, maritime policy, and maritime trade management in the XVI—XVII centuries.MethodThis study used historical research methods including heuristics, source criticism, interpretation, and historiography. The sources of data used were local sources (lontara) and foreign sources (Portuguese, Dutch, and English) to answer the three problems mentioned above by placing Makassar as the subject of the Nusantara spice route.Results/FindingsThe results of the study are: 1) the port growth arrangement the Makassar authorities did was by responding to the global trade dynamics around the spice route, such as focusing on structuring its ports as the centre of the Maluku spice trade. Second, maritime policy was implemented through free ports and the principle of Mare Liberum to advance Makassar to become an entrepot and a cosmopolitan world city. Third, the codification of Ammana Gappa's shipping and trade laws in Makassar further strengthens the maritime identity of the Makassarese, Bugis, and Mandar people in building the spice route of the Archipelago.ConclusionStarting from the perspective of the archipelago as a subject, this study shows the role of Makassar in promoting the spice route. Studies like this can also be developed at other ports on the spice route, thereby strengthening the archipelago's contribution to the history of the world's spice routes.